Protective Effects of Anti-IL17 on Acute Lung Injury Induced by LPS in Mice - Righetti, Renato Fraga; Santos, Tabata Maruyama dos; Camargo, Leandro do Nascimento; Aristóteles, Luciana Ritha Cássia Rolim Barbosa; Fukuzaki, Silvia; Souza, Flávia Castro Ribas de; Santana, Fernanda Paula Roncon; Agrela, Marcus Vinicius Rodrigues de; Cruz, Maysa Mariana; Alonso-Vale, Maria Isabel Cardoso; Genaro, Isabella Santos; Saraiva-Romanholo, Beatriz Mangueira; et al. (Frontiers in Pharmacology, 2018)
Introduction: T helper 17 (Th17) has been implicated in a variety of inflammatory lung and immune system diseases. However, little is known about the expression and biological role of IL 17 in acute lung injury (ALI). We investigated the mechanisms involved in the effect of anti-IL17 in a model of lipopolysaccharide (LPS)-induced acute lung injury (ALI) in mice. Methods: Mice were pre-treated with anti-IL17, 1h before saline/LPS intratracheal administration alongside non-treated controls and levels of exhaled nitric oxide (eNO), cytokine expression, extracellular matrix remodeling and oxidative stress, as well as immune cell counts in bronchoalveolar lavage fluid (BALF), and respiratory mechanics were assessed in lung tissue. Results: LPS instillation led to an increase in multiple cytokines, proteases, nuclear factor-κB and Forkhead box P3 (FOXP3), eNO and regulators of the actomyosin cytoskeleton, the number of CD4+ and iNOS-positive cells as well as the number of neutrophils and macrophages in BALF, resistance and elastance of the respiratory system, ARG-1 gene expression, collagen fibers, and actin and 8-iso-PGF2α volume fractions. Pre-treatment with anti-IL17 led to a significant reduction in the level of all assessed factors. Conclusions: Anti-IL17 can protect the lungs from the inflammatory effects of LPS-induced ALI, primarily mediated by the reduced expression of cytokines and oxidative stress. This suggests that further studies using anti-IL17 in a treatment regime would be highly worthwhile.